Catalyzing Transitions to Sociality: Ecology Builds on Parental Care - Socias-Martínez, Lluís; Kappeler, Peter M. (Frontiers in Ecology and Evolution, 2019)
In the context of social evolution research, a great emphasis on kin-selected benefits has led to understand parental care as one of the activities that helpers can perform in extended cooperative families. Nevertheless, this perspective might have precluded a deeper understanding of the implications of parental care for social evolution. We argue that parental care is a broader set of processes playing a key role both before and during the emergence of sociality. The care system of a species may be understood as the result of long coevolutionary processes with environmental pressures during pre-social stages that impact transitions to sociality. We evaluate the present framework against evidence on the evolution of parental care and transitions towards sociality in subsocial and parasocial vertebrate and invertebrate species. Moreover, following previous evidence for the importance of modes of foraging and resting we structure our inquiry by classifying societies into three types. Our results suggest that in central place foragers and fortress defenders, ecological factors promoting the evolution of parental care foster a set of coevolutionary feedback loops resulting in increases in parental effort and offspring needs. Offspring needs alone or in combination with limited breeding options enhance the relative benefits of positive social interactions, catalyzing social transitions. In itinerant foragers, sociality is associated with colonizing new niches. Changes in predation pressure entail changes in the modes of care or selection for certain types of care present already in solitary ancestors. Further changes in the form of collective defense may be needed for permanent sociality to evolve. We conclude there is evidence that social transitions to different types of societies are the result of long coevolutionary processes between environmental pressures and the care systems in a wide variety of taxa. Therefore, advances in the study of the origins of sociality may need from further investigation of parental care evolution in solitary ancestors of today's social species.